Spatiotemporal distribution of Vibrio parahaemolyticus in relation to environmental parameters in a coastal lagoon on the Pacific coast of northwestern Mexico - Ana M Rivas-Montaño; Irasema E Luis-Villaseñor; Pablo Piña-Váldez; Bruno Gómez-Gil; Marcial L Lizárraga-Partida (Ciencias Marinas, 2018)
Vibrio parahaemolyticus has been responsible for the increasing number of diarrhea cases in Sinaloa, Mexico, since 2003. We investigated the presence, distribution, and content of V. parahaemolyticus toxigenic genes detected in water, zooplankton, and sediment samples in relation to environmental variables in Caimanero Lagoon (Mazatlán, Sinaloa). Samples were analyzed by PCR to detect the presence of V. parahaemolyticus and its toxigenic factors. Of all the samples analyzed, 57.5% tested positive for thermolabile hemolysin (tlh), a gene indicative of the species. The thermostable direct hemolysin (tdh) and tdh-related hemolysin (trh) genes, which are both pathogenicity markers of this species, were detected in 9% and 6% of the samples, respectively. The orf8 fragment, which has been recently detected in pandemic strains (O3:K6), was detected in 11% of the samples. Vibrio parahaemolyticus was detected more frequently in zooplankton, with the highest incidence observed in February. Salinity was positively correlated with V. parahaemolyticus; however, no correlation was found between V. parahaemolyticus and temperature. The presence of toxigenic V. parahaemolyticus during the different seasons indicates the need to maintain continuous sanitary inspection of fish products from Caimanero Lagoon.